2018
DOI: 10.18203/2394-6040.ijcmph20182185
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal, intranatal and postnatal care: a tertiary centre study of North India

Abstract: Background:Care of pregnant lady during antenatal period is the key to reducing maternal mortality and morbidity during pregnancy and child birth and futher improving the growth and development of the newborn. Optimal weight gain in the initial 6 months is very essential. Therefore, study aims to assess antenatal, intranatal and postnatal factors affecting the growth of newborn child. Methods:A Community based cross sectional study was conducted twice – at delivery and second after 6 months. A total of 220 lad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…6,[13][14][15] It was observed in present study that 91% of the mothers received iron and folic acid supplementation, this results are quite comparable to the observation of NFHS-4, the percentage of women who either received or bought IFA tablets was 77.7%, Gupta et al study reported that 93.7% mothers received IFA tablets and Gandhi et al study also revealed that all the mothers had received Iron supplements during ANC visit. 6,[16][17][18] In the present study 95% of mothers immunized with adequate dose of Tetanus Toxoid, this findings is relatively compared to the result of Annual Health Survey (AHS) 2012-13 Uttar Pradesh and Lucknow district which is 83.2% and 87.5% respectively and also supported by some others Indian authors in their study. 6,19,20 In the present study, 75.5% mothers were delivered in health facility in which 52% at Government health facility and 24% in private health facility while 24.5% mothers were delivered at home.…”
Section: Discussionsupporting
confidence: 83%
“…6,[13][14][15] It was observed in present study that 91% of the mothers received iron and folic acid supplementation, this results are quite comparable to the observation of NFHS-4, the percentage of women who either received or bought IFA tablets was 77.7%, Gupta et al study reported that 93.7% mothers received IFA tablets and Gandhi et al study also revealed that all the mothers had received Iron supplements during ANC visit. 6,[16][17][18] In the present study 95% of mothers immunized with adequate dose of Tetanus Toxoid, this findings is relatively compared to the result of Annual Health Survey (AHS) 2012-13 Uttar Pradesh and Lucknow district which is 83.2% and 87.5% respectively and also supported by some others Indian authors in their study. 6,19,20 In the present study, 75.5% mothers were delivered in health facility in which 52% at Government health facility and 24% in private health facility while 24.5% mothers were delivered at home.…”
Section: Discussionsupporting
confidence: 83%